STUDI PUSTAKA: PENGAWASAN AKADEMIK OLEH KEPALA UNTUK MENINGKATKAN KUALITAS PENDIDIK - Yolviansyah, Fauziah; Hermanto, Hermanto (EduFisika: Jurnal Pendidikan Fisika, 2023)
Academic supervision is one of the main tasks and responsibilities of the principal. This research aims to look at academic supervision in physics education and the quality of education. The quality of educators is a topic of discussion in educational management. Educators play a role in improving the quality of education because educators are the parties who participate in the teaching and learning process and are closest to students. Supervision of academic leadership positively impacts improving the quality of education. In this case, empowering educational leadership can improve functional abilities so that school principals can serve in accordance with their authority and responsibilities and manage all school activities to run well and function optimally. This study uses the literature review method, which looks at the problems around it.